Case report: 125I seed implantation for rare malignant solitary fibrous tumor in the pelvic cavity: a case report - Gao, Zhen; Yu, Huimin; Di, Xuemin; Zhao, Jinxin; Liang, Yansong; Liu, Zezhou; Wang, Juan; Zhang, Hongtao (Frontiers in Oncology, 2022)
Solitary fibrous tumor (SFT) is a rare spindle cell tumor, benign or low-grade malignant, with an extremely low possibility of occurrence of malignant solitary fibrous tumor (MSFT). Surgery is an effective way for treating SFT, but it is often difficult to resect completely due to a large size, with a high recurrence rate and mortality rate after operation. Additionally, SFT is relatively resistant to chemotherapy, and there is a lack of effective systemic drug treatment. These lead to certain difficulties in the treatment of SFT. We report a case of a rare MSFT in the pelvic cavity. With a history of recurrence after two surgeries, this patient underwent surgical removal combined with 125I seed implantation at our hospital in the context that the tumor could not be completely removed because it was large and adhered to surrounding tissues; after up to 43 months of progression-free survival (PFS), the patient underwent 125I seed implantation alone, and achieved a complete remission, with a PFS up to 35 months. 125I seed implantation can be a safe and effective treatment option for unresectable MSFT as well as a potential solution to repeated local recurrence.